2006
DOI: 10.1111/j.1365-2559.2006.02490.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus‐induced B‐cell proliferation of Hodgkin's and Reed–Sternberg cell pheno‐ and genotype may develop in peripheral T‐cell lymphomas

Abstract: 1. Brissett AE, Olsen KD, Kasperbauer JL et al. Merkel cell carcinoma of the head and neck: a retrospective case series. Head Neck 2002; 24; 982-988. 2. Moll I, Zieger W, Schmelz M. Proliferative Merkel cells were not detected in human skin. Arch. Dermatol. Res. 1996; 288; 184-187. 3. Llombart B, Monteagudo C, Lopez-Guerrero JA et al. Clinicopathological and immunohistochemical analysis of 20 cases of Merkel cell carcinoma in search of prognostic markers. Histopathology 2005; 46; 622-634. 4. Fernandez-Figueras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…This phenotype under these circumstances-CD45, TF and EBNA-2 negativity beside CD30, LMP-1 positivity being the most importanthas not been described yet in the literature available for us, in fact CD45 expression data were not always available and the IgH-TFs have not been investigated at all in the referred papers. Our observations-together with previous result on the molecular characteristics of FRI-CDRIII region in the IgH gene of sorted LBCs in such a case-imply that EBV infected LBCs indistinguishable in morphology, pheno-and genotype from those of HRS cells in cHL may also arise in TLs [3]. These cases should not be called TL composite with cHL as the unique, reactive cellular background of cHL was missing.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…This phenotype under these circumstances-CD45, TF and EBNA-2 negativity beside CD30, LMP-1 positivity being the most importanthas not been described yet in the literature available for us, in fact CD45 expression data were not always available and the IgH-TFs have not been investigated at all in the referred papers. Our observations-together with previous result on the molecular characteristics of FRI-CDRIII region in the IgH gene of sorted LBCs in such a case-imply that EBV infected LBCs indistinguishable in morphology, pheno-and genotype from those of HRS cells in cHL may also arise in TLs [3]. These cases should not be called TL composite with cHL as the unique, reactive cellular background of cHL was missing.…”
Section: Discussionsupporting
confidence: 54%
“…In those cases, however, the large cells always expressed at least one Tcell markers and atypical T-phenotype being concordant to that of the background T-lymphoma cells, furthermore, they proved to be negative for EBV. If the large cells in a TL are consistently negative for several T-cells markers, but positive for EBV, an accompanying or secondary B-cell proliferation might be suspected, which have been described with phenotypic heterogeneity and some controversy regarding the genotypic features [2,3,6,10,11]. Quintanilla-Martinez et al (1999) analyzed three such cases and found for the scattered large cells either an activated Bcell (CD15−, CD30+, CD20+) or cHL-HRS cell (CD15+, CD30+, CD20+) phenotype, polyclonal / oligoclonal IgH-R in microdissected cells and no progression to disseminated cHL.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…94,95 Σε σπάνιες περιπτώσεις από αυτά τα EBV(+) κύτταρα μπορεί να προκύψει ένα διάχυτο λέμφωμα από Β-μεγάλα κύτταρα ή ακόμη και λέμφωμα με μορφολογικά και ανοσοϊστοχημικά χαρακτηριστικά κλασσικού λεμφώματος Hodgkin. [96][97][98][99][100][101] Επίσης λεμφώματα και λεμφοϋπερπλαστικές νόσοι που αναπτύσσονται σε ανοσοκαταστολή (πρωτοπαθής ανοσοκαταστολή, ή μετά από μεταμόσχευση, ή θεραπεία από μεθοτρεξάτη,) μπορεί να προσομοιάζουν το λέμφωμα Hodgkin. Η WHO ταξινόμηση στις καταστάσεις αυτές περιλαμβλάνει λέμφωμα Hodgkin και Hodgkin-like λεμφώματα.…”
Section: διαφορική διάγνωσηunclassified